Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.